Pengaruh Penggunaan Media Big Book terhadap Keterampilan Membaca Permulaan Siswa Kelas I Sekolah Dasar Negeri 75 Pontianak Barat - Elfariani, Elfariani; Halidjah, Siti; Pranata, Rio (FONDATIA, 2023)
Beginning reading is the initial stage for students to recognize letter symbols in a simple scope. The use of appropriate media in learning can raise enthusiasm in learning to read early. The purpose of this study was to obtain information about the effect of using big book media on the initial reading skills of grade I students at State Elementary School 75 West Pontianak. The method used in this study is an experimental method with the form of Experimental Quasy. The number of samples in this study was 60 students from 91 students selected using purposive sampling.techniques. In collecting research data using measurement techniques and data collection tools in research is a test in the form of a preliminary.reading.test. The data analysis used is using the mean and t-test. The results of the study can be concluded that: (1) There is an influence on students' initial reading skills after being taught using big book media in grade I students of State Elementary School 75 West Pontianak; (2) There was a significant difference between the use of big.book media on.students'.initial reading skills in experimental and control classes.